The genes and the environment in nasal allergy. Issue 5 (October 2015) - Chiarella, Sergio E.; Fernandez, Rafle; Avila, Pedro C.
<x xml:space="preserve">Abstract</x> Purpose of review In this review, we summarize the latest publications on the genetic and environmental determinants of allergic rhinitis. Recent findings Recent advances in genetic technology and bioinformatics have enabled simultaneous unbiased analysis of the entire genome regarding DNA sequence variants, epigenetic modifications and gene expression, providing functional correlates for DNA variants and phenotypes. As a result, new genes of mitochondrial and B-lymphocyte metabolism have been associated with allergic rhinitis phenotypes. Epidemiological studies recently showed an increased risk to develop allergic rhinitis in all age groups with reduction in farm exposure and in children with few older siblings. Climate changes seem to have also influenced pollen exposure and pollen-induced allergic disease. Lastly, occupational rhinitis has been increasingly recognized as a large burden to society. Summary In summary, new high throughput genetics research technologies have pointed to new previously unsuspected pathways that may modulate the risk of developing allergic rhinitis such as mitochondrial metabolism. In addition, recent environmental factors found to influence the risk of developing allergic rhinitis include exposure to farm, pollution, occupational agents, and changes in climate.